Opening the Black Box of Editorship - Baruch, Y.; Konrad, A.; Aguinis, H.; Starbuck, W.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
Understanding the roles of editors, and the processes of editorship in knowledge dissemination, are highly relevant issues for most scholars. Written by leading scholars with strong editorial experience, this book will serve as a guide for editors and scholars wishing to become editors in management and behavioural sciences.
Keywords: Management; Economics; Management science; Project management; Management; Economics, general; Project Management